New decade, new response: Altering the public health response to toxigenic cutaneous diphtheria. (30th September 2020) - Marshall, N C; Baxi, M; MacDonald, C; Sikora, C; Tyrrell, G J
Abstract: Background: Classical diphtheria is a potentially fatal respiratory disease mediated by the diphtheria toxin of Corynebacterium diphtheriae. Due to high vaccination rates against this toxin in Canada, the national incidence of respiratory diphtheria is near zero, and the toxin plays no recognized role in cutaneous diphtheria. Therefore, in this study, we assessed the diagnostic and public health benefits of diphtheria toxin testing and cutaneous diphtheria investigations in a highly vaccinated population. Methods: Over the last 10 years, we retrospectively determined: the number of C. diphtheriae isolates identified in the province of Alberta, Canada; the disease state of each individual tested (disease vs asymptomatic carrier); the source (cutaneous vs respiratory); and the number of toxin tests performed. Results: In 10 years, zero cases of respiratory diphtheria and three cases of toxigenic cutaneous diphtheria were identified. Despite zero cases of respiratory disease, diphtheria toxin testing significantly increased (p = 0.0001), with 86% of toxin tests performed on cutaneous isolates. Subsequent public health investigations of each case of toxigenic cutaneous diphtheria mandated the collection of 315 total specimens from 92 individuals, revealing low rates of C. diphtheriae colonization among contacts and no further cases. Conclusions: This study challenges the value of reflexive diphtheria toxin testing in uncomplicated cutaneous diphtheria among highly vaccinated populations. Cutaneous diphtheria investigations demanded disproportionate public health and laboratory resources and demonstrated a discrepancy between toxin pathophysiology and disease. Therefore, we recommend stewarding diphtheria toxin tests for toxin-mediated disease forms and ensuring adequate vaccination. This approach would spare public health and laboratory resources by customizing responses around the role of the diphtheria toxin in each form of disease. Key messages: Investigations for cutaneous diphtheria increased demand for toxin testing in Alberta, Canada, though the toxin plays no role in this form of disease. In populations with high vaccination rates against diphtheria toxoid, cutaneous diphtheria cases do not require additional laboratory testing for the presence of the diphtheria toxin.